Pregnancy-related malaria prevention with insecticide-treated nets (ITNs) : a review of the relevant literature - Yulizawati, Yulizawati; Silmi, Harridhil; Intasir, M. Pemberdi (Universitas Andalas, 2023)
Introduction: Every year, an estimated 125 million pregnancies are at risk of contracting malaria. Malaria poses a risk to both the mother and the fetus since pregnant women are more likely to get it than non-pregnant women. Newborns, fetuses, and pregnant women are all susceptible to malaria infection. It is frequently associated with anemia, intrauterine growth restriction (IUGR), and issues such as low birth weight and trans placental parasitemia. From the first point of contact, insecticide-treated nets (ITNs) can help shield the pregnant mother and her unborn child from malaria. Methods: A range of English-language journal articles and case studies were reviewed in the development of this literature reviewÂ that were released after 2018 in the field of study. Electronic searches were performed on a number of databases, including ScienceDirect and PubMed. Results: A screening procedure was carried out on 189 articles to show that the sources used were relevant and useful. Ultimately, it was determined that 5 papers would serve as the sources for this literature study. ITNs are an effective way to reduce the negative outcome for pregnant mothers who catch malaria during pregnancy, as our assessment of the literature has shown. Studies demonstrate the efficacy of ITNs in reducing the likelihood of unfavorable consequences for expectant mothers who catch malaria during pregnancy.Â Conclusion: the efficiency of ITNs in reducing the likelihood that pregnant women who catch malaria during pregnancy will experience unfavorable outcomes. Encouragement of husbands and other important family members to support their spouses' use of ITNs . Reiterating the policy's emphasis on malaria prevention education as a critical element is required to boost the use of free ITNs in healthcare settings